Nystagmus in pediatric patients: interventions and patient-focused perspectives - Penix K (Dove Medical Press, 2015)
Kimberly Penix,1 Mark W Swanson,1 Dawn K DeCarlo1,2 1School of Optometry, 2Department of Ophthalmology, School of Medicine, University of Alabama at Birmingham, Birmingham, AL, USA Abstract: Nystagmus refers to involuntary, typically conjugate, often rhythmic oscillations of the eyes. The most common cause of nystagmus in children is infantile nystagmus syndrome (INS). INS presents within the first few months of life and is sometimes accompanied by an ocular condition associated with sensory impairment. Because this condition affects a person throughout life, it is important to understand the options available to manage it. This review focuses on the underlying nystagmus etiology, psychosocial and functional effects of nystagmus, as well as current principles of management, including optical, pharmacological, surgical, and rehabilitative options. Currently, the neural mechanisms underlying INS are not fully understood. Treatment options are designed to increase foveation duration or correct anomalous head postures; however, evidence is limited to mainly pre- and post-study designs with few objective comparisons of treatment strategies. Management of INS should be individualized. The decision on which treatment is best suited for a particular patient lies with the patient and his/her physician. Keywords: nystagmus, infantile nystagmus syndrome, vision impairment, pediatric, quality of life